Maternal Healthcare Financing: Gujarats Chiranjeevi Scheme and Its Beneficiaries (Journal of Health, Population and Nutrition, 2009)
Maternal mortality is an important public-health issue in India, specifically in Gujarat. Contributing factors are the Government's inability to operationalize the First Referral Units and to provide an adequate level of skilled birth attendants, especially to the poor. In response, the Gujarat state has developed a unique public-private partnership called the Chiranjeevi Scheme. This scheme focuses on institutional delivery, specifically emergency obstetric care for the poor. The objective of the study was to explore the targeting of the scheme, its coverage, and socioeconomic profile of the beneficiaries and to assess financial protection offered by the scheme, if any, in Dahod, one of the initial pilot districts of Gujarat. A household-level survey of beneficiaries (n=262) and non-users (n=394) indicated that the scheme is well-targeted to the poor but many poor people do not use the services. The beneficiaries saved more than Rs 3,000 (US$ 75) in delivery-related expenses and were generally satisfied with the scheme. The study provided insights on how to improve the scheme further. Such a financing scheme could be replicated in other states and countries to address the cost barrier, especially in areas where high numbers of private specialists are available. Key words: Chiranjeevi scheme; Delivery; Emergency obstetric care; Maternal mortality; Obstetric care; Private-public relationship; India doi: 10.3329/jhpn.v27i2.3367 J Health Popul Nutr 2009 April;27(2):249-258